1993
DOI: 10.1152/ajprenal.1993.265.3.f425
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous EGF as a potential renotrophic factor in ischemia-induced acute renal failure

Abstract: The time course for the increases in soluble renal epidermal growth factor (EGF) after ischemia has been established. These elevated levels of EGF have been compared with the degree of tissue injury as well as the extent of cell proliferation in the recovering tissue. Levels of soluble immunoreactive EGF (irEGF) in control animals were 9.74 +/- 1.1 ng/g wet wt (n = 4-8 for all values) and rose to 83.9 +/- 30 ng/g within 12 h after injury. Soluble irEGF content peaked at 88.8 +/- 15 ng/g at 24 h postinjury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…In the study presented here, we provide evidence that EGF leads to activation of transcription factor NF-B in quiescent proximal tubule cells (HK-2) in vitro. In these cells, EGF exhibits growth-inducing properties similar to what has been described before (11,22,64,69), suggesting that Although the kidney is a major site for synthesis of prepro-EGF, and EGF receptor expression is upregulated at the site of injury, it is remarkable that EGF mRNA levels decrease at the initial time points of renal injury (18,22,28,32,58,59). The temporary lack of EGF in this context could result in a significant deficit of survival factors (48,49,53,54).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the study presented here, we provide evidence that EGF leads to activation of transcription factor NF-B in quiescent proximal tubule cells (HK-2) in vitro. In these cells, EGF exhibits growth-inducing properties similar to what has been described before (11,22,64,69), suggesting that Although the kidney is a major site for synthesis of prepro-EGF, and EGF receptor expression is upregulated at the site of injury, it is remarkable that EGF mRNA levels decrease at the initial time points of renal injury (18,22,28,32,58,59). The temporary lack of EGF in this context could result in a significant deficit of survival factors (48,49,53,54).…”
Section: Discussionsupporting
confidence: 53%
“…This process is characterized by an increase in mitotic activity in renal epithelial cells and induction of nucleic acid synthesis (32). A burst of DNA synthesis is typical for all nephrotoxic or ischemic injuries, differing only in its rate and extent (59).…”
mentioning
confidence: 99%
“…Our study focused on mature EGF (6.3 kD), which is biologically active and has a renotrophic action in ischemic rat kidneys [21], and its expression is decreased in rat kidneys with CsA treatment [22]. The molecular mechanism of EGF as a growth factor was studied extensively in an experimental model of I/R injury, and data exist in favor of an involvement of EGF in regenerative hyperplasia after renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In rat kidneys with I/R injury, EGF immunoreactivity detected by immunohistochemical study decreases [27, 28, 29]but concentration of mature EGF rose 7- to 10-fold [21]. At the mRNA level, the EGF precursor [30]and prepro EGF mRNA [31]are decreased during renal tubular regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…1b). Since it has been reported that the level of soluble renal EGF elevates after reperfusion [14], we examined the level of EGF in the soluble fraction. However, we did not detect the band of soluble EGF in this condition (data not shown).…”
Section: Resultsmentioning
confidence: 99%